Cognitive-coordination training: impact on sport-specific physical fitness and technical skill of adolescent basketball athletes - Li, Qiner; Fu, Quan; Li, Longhui; Wang, Jingyi (Frontiers in Psychology, 2026)
BackgroundCoordination ability is crucial for athletic performance, particularly in basketball, which demands rapid decision-making under high cognitive load. However, few studies have examined systematic training that integrates cognitive and coordination components. This study investigated the effects of a 12-week Cognitive-Coordination Training (CCT) program on sport specific physical fitness and technical skills in adolescent basketball players.MethodsThirty-two sub-elite basketball players were randomly assigned to an experimental group (EG, n = 16) or control group (CG, n = 16). The EG performed three 30-min CCT sessions weekly, embedded within the regular warm-up routine—replacing part but not all of it—while the CG followed standard training. Both groups completed pre- and post-tests of sport specific fitness (SR, AJT, DJR, SJTP) and technical skills (FDL, MPR, HSD).ResultsNo significant pre-intervention differences were found. After 12 weeks, the EG showed significantly greater improvements than the CG across all tests (p < 0.001). Within group analysis revealed significant gains in all measures for the EG (p < 0.001), while the CG showed smaller improvements in only four tests and in the overall mean score.ConclusionThe 12-week Cognitive-Coordination Training, embedded within the warm-up phase, effectively enhanced sport specific fitness and technical performance in sub-elite youth basketball players. By integrating cognitive processing with motor coordination, this approach offers a practical and theoretically grounded method for optimizing athletic performance and complements traditional basketball training models.